Radioiodine (131I) therapy in a child with autism spectrum disorder: A complex and demanding task - Giovanni Bibbo; Ian Kirkwood; Victoria Sigalas; Tracy Benger (World Journal of Nuclear Medicine)
In January 2017, an 11.5-year-old male child with autism was referred for radioiodine (RAI) therapy post total thyroidectomy for papillary thyroid carcinoma. The treatment required swallowing a RAI capsule and remaining isolated (48–72 h). Initially, obstacles to a successful treatment seemed insurmountable as he had complex needs and behavioral issues due to his autism, mild intellectual disability, and family environment. His mother was adamant that he would not be able to swallow the capsule and comply with the required isolation period. A multidisciplinary team was formed to explore options for successful treatment. Each option considered had its own risks and challenges. Behavioral therapy was considered to be the only possible option. It was pursued with regular, frequent contact between the child, his parents, and members of the team for counseling and behavioral modification, familiarization of the child with the staff, procedures, trial visits, and admission. The patient was successfully treated in October 2017.